Predicting recurrence of papillary thyroid cancer using the eighth edition of the AJCC/UICC staging system. Issue 7 (23rd April 2019) - Chereau, N.; Oyekunle, T. O.; Zambeli‐Ljepović, A.; Kazaure, H. S.; Roman, S. A.; Menegaux, F.; Sosa, J. A.
Abstract : Background: The AJCC/UICC classification is widely used for predicting survival in papillary thyroid cancer (PTC), but has not been evaluated as a predictor of recurrence. The hypothesis of this study was that the eighth edition of the AJCC system can be used in this novel way. Methods: All patients in the study underwent surgery for PTC at a high‐volume endocrine surgery centre in France between 1985 and 2015. The seventh and eighth editions of the AJCC/UICC staging system for PTC were employed to predict recurrence and disease‐specific survival using the Kaplan–Meier and log rank tests. Results: Among 4124 patients (79·7 per cent female), median age was 50 (i.q.r. 38–60) years; 3906 patients (94·7 per cent) underwent total thyroidectomy, with lymph node dissection in 2495 (60·5 per cent). The eighth edition of the AJCC/UICC staging system placed 91·8, 7·1, 0·4 and 0·7 per cent of patients in stages I–IV respectively. After reclassifying patients from the seventh to the eighth AJCC/UICC edition, the disease was downstaged in 23·8 per cent. Over a median follow‐up of 7 years, 260 patients (6·4 per cent) developed recurrent disease, including 5·2 per cent of patients with stage I, 19·6 per cent with stage II, 59 per cent with stage III and 50 per cent with stage IV disease, according to the eighth edition. The eighth edition was a better predictor of recurrence than the seventh edition. Conclusion: The eighth edition of the AJCC/UICC staging system appears to be a novel tool for predicting PTC recurrence, which is a meaningful outcome for this indolent disease. The eighth edition can be used to risk‐stratify patients, keeping in mind that other molecular and pathological predictive factors must be integrated into the assessment of recurrence risk. Abstract : This study evaluated the new AJCC staging system, 8th edition, which was implemented on 1 January 2018, for its ability to predict recurrence of well differentiated thyroid cancer. This is a new application, as AJCC was originally designed for predicting survival. The authors used a single‐centre prospective cohort from France, and applied staging to patients who underwent surgery for papillary thyroid cancer from 1985 to 2015. Useful tool